Calculated initial parenteral treatment of bacterial infections: Bacterial gastrointestinal infections - Mutters, Reinier (GMS Infect Dis, 2020)
This is the fourteenth chapter of the guideline “Calculated initial parenteral treatment of bacterial infections in adults – update 2018” in the 2(nd) updated version. The German guideline by the Paul-Ehrlich-Gesellschaft für Chemotherapie e.V. (PEG) has been translated to address an international audience. Bacterial gastrointestinal infections are still the leading cause of death worldwide. The chapter describes the etiology of bacterial gastrointestinal infections in Germany and their frequency. Recommendations are given for the calculated therapy of these infections and for targeted antibiotic therapy for known pathogens. Particular attention is paid to Clostridium difficile. The diagnostic and therapeutic options of antibiotic therapy of the various infection patterns in this pathogen are discussed.